Calibration of a desktop scanner and digital image analysis procedure for quantification of root morphology - A. SIMOJOKI (Agricultural and Food Science, 2008)
Methodological tests with dark metal wires and barley roots showed that selecting proper scanner brightness adjustment is crucial when calibrating a desktop scanner for digital image analysis of root morphology. At high brightness the digitization of roots was incomplete, and thus the real length and width of the roots were underestimated. Lowering of the brightness improved the digitization, whereas stronger staining of the roots alone was not effective. Inaccurate results were produced also, if the size of the scanned sample was too large. The variation caused by the scanning and image analysis itself was minimal. A small amount of dry matter was lost from the roots during the preservation in the ethanol solution for several months before scanning. If absolute data on root masses are required, this loss cannot be neglected. Subsampling is strongly recommended to reduce the time required for the procedure. ;